2006
DOI: 10.1534/genetics.106.065102
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Patterns of Nucleotide Diversity, Linkage Disequilibrium and Demographic History of Norway Spruce [Picea abies (L.) Karst]

Abstract: DNA polymorphism at 22 loci was studied in an average of 47 Norway spruce [Picea abies (L.) Karst.] haplotypes sampled in seven populations representative of the natural range. The overall nucleotide variation was limited, being lower than that observed in most plant species so far studied. Linkage disequilibrium was also restricted and did not extend beyond a few hundred base pairs. All populations, with the exception of the Romanian population, could be divided into two main domains, a BalticoNordic and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
237
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(279 citation statements)
references
References 71 publications
40
237
1
1
Order By: Relevance
“…Lastly, the F ST values of SNPs did not deviate significantly from neutral expectations based on the Bayesian F ST test. Our results are in line with recent data obtained in various species, in which differentiation of CGs was compared with differentiation of neutral markers and of the target trait (Eveno et al (2008) in P. pinaster; Pyhäjärvi et al (2008) in P. sylvestris; Heuertz et al (2006) in Picea abies; Hall et al (2007) and Luquez et al (2007) in P. tremula). In all these case studies, the mean differentiation of genes was of the same level as differentiation of the neutral markers and far less than differentiation of the target trait.…”
Section: Differentiation Of Cgs Versus Trait Differentiationsupporting
confidence: 92%
“…Lastly, the F ST values of SNPs did not deviate significantly from neutral expectations based on the Bayesian F ST test. Our results are in line with recent data obtained in various species, in which differentiation of CGs was compared with differentiation of neutral markers and of the target trait (Eveno et al (2008) in P. pinaster; Pyhäjärvi et al (2008) in P. sylvestris; Heuertz et al (2006) in Picea abies; Hall et al (2007) and Luquez et al (2007) in P. tremula). In all these case studies, the mean differentiation of genes was of the same level as differentiation of the neutral markers and far less than differentiation of the target trait.…”
Section: Differentiation Of Cgs Versus Trait Differentiationsupporting
confidence: 92%
“…For instance, Heuertz et al (2006) found that across large geographic distances, Picea abies is strongly differentiated across large geographic barriers, with F ST estimates approaching those that we found among genetic groupings. Therefore, even though many forest trees have extensive potential for long-distance dispersal (Savolainen et al, 2007), they can still develop strong neutral genetic structure across large spatial scales and geographic barriers.…”
Section: Population Structuresupporting
confidence: 67%
“…Other North American tree species support the hypothesis of impacts of past climate on population sizes and distributions. In a latitudinally oriented study of Picea sitchensis, Holliday et al (2010) found support for an historical bottleneck and expansion, and also found negative Tajima's D, as did a study of Picea aibes in Eurasia (Heuertz et al, 2006). In P. trichocarpa of the central and northern Pacific Northwest, populations have expanded rapidly since the LGM (Zhou et al, 2014).…”
Section: Population Structurementioning
confidence: 96%
“…It can also be the consequence of demographic changes influencing diversity in the entire genome, like population growth after an ancient bottleneck (Holliday, Yuen, Ritland, & Aitken, 2010). Population size reduction during the last glacial period and population growth after this bottleneck has shaped demography in other tree species (Heuertz et al., 2006; Holliday et al., 2010; Ingvarsson, 2008; Pyhäjärvi et al., 2007; Zhou et al., 2014) and is also a plausible scenario for P. deltoides , but demography has not been assessed in this species to date. In the absence of a demographic study in P. deltoides and because demography can confound signatures of selection causing false‐positive Tajima's D outliers, this statistic was used to complement the information obtained with other tests.…”
Section: Discussionmentioning
confidence: 99%